2022
DOI: 10.1111/ajag.13040
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2020 New Zealand COVID‐19 lockdown on participants in a community‐based, peer‐led fall prevention program

Abstract: Objectives To explore the impacts of the 2020 New Zealand COVID‐19 lockdown on peer‐led Steady as You Go (SAYGO) fall prevention exercise classes and members, and to develop recommendations for mitigating impacts during future lockdowns. Methods Semi‐structured phone interviews were conducted with 20 SAYGO program participants and managers following the first COVID‐19 lockdown in New Zealand. Interviews were audio‐recorded, transcribed verbatim and analysed using the Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…There has been much work and research on fall risk factors and efficacious interventions, such as exercise, to improve strength and balance to reduce fall risk. One such intervention described in this virtual issue by Smith et al 3 is the Steady As You Go program in New Zealand. This model uses peer‐led community‐based strength and balance classes to reduce fall risk in older adults.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There has been much work and research on fall risk factors and efficacious interventions, such as exercise, to improve strength and balance to reduce fall risk. One such intervention described in this virtual issue by Smith et al 3 is the Steady As You Go program in New Zealand. This model uses peer‐led community‐based strength and balance classes to reduce fall risk in older adults.…”
mentioning
confidence: 99%
“…There has been much work and research on fall risk factors and efficacious interventions, such as exercise, to improve strength and balance to reduce fall risk. One such intervention described in this virtual issue by Smith et al 3 Māori to age stronger. The initial trial showed statistically significant reductions in fall risks (e.g.…”
mentioning
confidence: 99%